2022
DOI: 10.3389/fphys.2022.1039591
|View full text |Cite
|
Sign up to set email alerts
|

Effects of blood flow restriction training on anthropometric and blood lipids in overweight/obese adults: Meta-analysis

Abstract: Purpose: To systematically evaluate the effects of blood flow restriction training (BFRT) on anthropometric indicators and blood lipids in overweight/obese adults.Methods: A literature search was conducted on PubMed, Web of Science, Embase, Scopus, SPORTDiscus and Cochrane Library databases to determine the final literature based on inclusion and exclusion criteria. Review Manager 5.4.1 was used to evaluate the quality of the literature based on the Cochrane bias risk assessment tool, and Stata 17.0 software w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
2
2
0
Order By: Relevance
“…This is consistent with the research findings of Sun et al. ( 38 ). Abdominal obesity in elderly T2DM patients is often accompanied by more serious dyslipidemia ( 39 , 40 ).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This is consistent with the research findings of Sun et al. ( 38 ). Abdominal obesity in elderly T2DM patients is often accompanied by more serious dyslipidemia ( 39 , 40 ).…”
Section: Discussionsupporting
confidence: 94%
“…This indicated that the two types of exercise could effectively reduce fat, especially abdominal fat, to achieve the goal of optimizing body shape and blood lipids. This is consistent with the research findings of Sun et al (38). Abdominal obesity in elderly T2DM patients is often accompanied by more serious dyslipidemia (39,40).…”
Section: Discussionsupporting
confidence: 93%
“…Alternatively, blood flow restriction exercise (BFRE), characterized by reduced mechanical load, also reduces body weight, body fat content, waist circumference, cholesterol, and LDL in overweight/obese adults and improves glycemic control in humans with the metabolic syndrome [25,26].…”
Section: Metabolic Effects Of Exercisementioning
confidence: 99%
“…This produces the effect of intensive training while using lower resistance or endurance exercises. Previous studies have demonstrated that blood flow restriction training can increase muscle mass and strength, improve muscle fitness, aerobic capacity, knee rehabilitation, acute bone formation markers and hormonal responses, and athletic performance in various populations (Korkmaz et al, 2022;Sun., 2022;Bemben et al, 2022). However, there is limited research on the effects of low-intensity resistance training combined with blood flow restriction on muscle mass and strength in overweight adolescents.…”
Section: Introductionmentioning
confidence: 99%